Estratégia global-local aplicada ao método dos elementos finitos generalizados - Phillipe Daniel Alves (2012)
The aim of this work is to generalize the implementation of Global-Local Generalized Finite Element Method (GFEMgl) formulation. This generalization has been performed in INSANE (INteractive Structural ANalysis Environment), a computational environment developed by the Department of Structural Engineering (DEEs) at the Federal University of Minas Gerais (UFMG), which has been implemented using Object Oriented Programming (OOP). In the conventional version of GFEM, the shape functions of nite elements are hierarchically enriched by analytical functions, according to the problem behaviour. In GFEMgl, however, the enrichment functions are constructed numerically fromthe solution of a local problem. This approach allows the use of coarse global meshes around domains with complex stresses distribution. The local problem, however, can be rened by using a large number of elements and dierent enrichment functions. The results of the localproblem are used to enrich the global problem. The advantage of this approach is to allow a well-rened description of the local problem and avoiding an overburden for the computation of the global solution.